(Re)-Defining 'Teacher': Preservice Teachers with Disabilities in Canadian Teacher Education Programs. Issue 1 (18th April 2018) - Wilson, Alina; Sokal, Laura; Woloshyn, Deb
Abstract : Directors of Student Teaching from the Western Canadian provinces participated in focus groups about the realities and decision-making processes around practicum for preservice teachers with disabilities. Results showed current standards, when applied rigidly, served to reify a static, homogenous, and unrealistic definition of 'teacher' that marginalises preservice teachers with disabilities. However, the effort of directors to challenge this notion of 'teacher', framed within the constructionist model of disability, gives hope for a more inclusive future teaching force.